Karakteristik Biokomposit Foam Maizena dan Glukomanan pada Perlakuan Konsentrasi Campuran Sorbitol dan TDI-80 - Sarito, Ignatia Karolina; Hasojuwono, Bambang Admadi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): Desember, 2022)
This study aims to know the effect of the concentration of a mixture of sorbitol and TDI-80 on the characteristics of cornstarch and glucomannan foam biocomposite and to determine the concentration of a mixture of sorbitol and TDI-80 which produces the best characteristics of cornstarch and glucomannan foam biocomposite. This study used a completely randomized design (CRD) with 5 treatments with 4 repetitions so that there were 20 experimental units with variations in the mixture of sorbitol and TDI-80 (5%, 10%, 15%, 20% and R5 = 25%) with a ratio of 1:1. The data obtained were analyzed for diversity (ANOVA) and continued with the Tukey test using Minitab 17 software. The variables observed were hardness, bouncing spring, breaking stress, elongation at break, tear resistance, constant compression and biodegradation. The results showed that the concentration of the mixture of sorbitol and TDI-80 had an effect on mass density, hardness, bouncing spring and constant compression, breaking stress, elongation at break and tear resistance. The best cornstarch and glucomannan foam biocomposite was obtained in the treatment with a mixture of sorbitol and TDI-80 concentration of 25% with a hardness value of 5.15 kg, a constant compressive value of 3.15%, a mass density of 0.12 g/mL, and a rebound spring of 22.91. %, breaking stress 0.05 N/mm2, elongation at break 4.52%, tear resistance 0.04 N/cm 3 and biodegradation rate within 8 days days. Keywords: biocomposite foam, cornstarch, glucomannan, concentration of sorbitol and TDI-80.